Desire, need, and obligation: Examining commitment to luxury brands in emerging markets. Issue 3 (June 2022) - Singh, Jaywant; Shukla, Paurav; Schlegelmilch, Bodo B.
Abstract: The availability of a wide variety of luxury brands has resulted in declining commitment toward a single brand. Enhancing brand commitment has, therefore, become a significant challenge for international businesses and marketing managers. We develop a multi–dimensional brand commitment framework underpinned by marketing, organizational, and social psychology literature streams. The simultaneous examination of brand–commitment dimensions based on consumer desire, need, and obligation in our framework offers a novel perspective that advances research on brand commitment. Our findings demonstrate stability of the framework in important emerging markets for luxury brands, namely China, India, Russia, Turkey, and Thailand. The framework, incorporating affective, continuance, and normative brand commitment dimensions, offers a conceptually robust fit. We demonstrate that each brand commitment dimension is influenced by distinct antecedents, and we show the direct and interactional impact of consumers' emotional attachment, economic motivations, and normative pressures on purchase intentions. Supported by well-established theories in organizational and social psychology, our study offers new insights on how consumers commit to brands. We provide international brand managers with a blueprint for strengthening brand commitment across countries. Highlights: Enhancing consumer commitment toward brands is crucial for business success. A multi-dimensional model explains luxury brand commitment in emerging markets. Consumers' affective, continuance, and normative commitment impact brand purchases. International marketers could build luxury brand commitment with customized strategy.